Multiwell stiffness assay for the study of cell responsiveness to cytotoxic drugs. Issue 2 (6th September 2013) - Zustiak, Silviya; Nossal, Ralph; Sackett, Dan L.
ABSTRACT It is now well understood that the cell microenvironment, including the surrounding matrix, profoundly affects cell fate. This is especially true for solid tumors where, for example, matrix stiffness is believed to be an important factor in tumorogenesis. Our hypothesis is that since matrix stiffness affects cell fate, it may also be important in drug resistance. To test this hypothesis, we designed and built a multiwell polyacrylamide (PA) gel‐based stiffness assay, in which the gels were coated with collagen in order to facilitate cell attachment and proliferation. This PA‐based assay was used to examine the effect of stiffness on cultured cell responsiveness to cytotoxic drugs. In particular, we tested multiple cancer cell lines and their susceptibility to paclitaxel, a microtubule‐targeting agent. By assessing cell proliferation, morphology, and the IC50 of the drug, we were able to establish that the stiffness affects responsiveness to cytotoxic drugs in a cell‐dependent manner. Biotechnol. Bioeng. 2014;111: 396–403. © 2013 Wiley Periodicals, Inc.